Walkability: From Spatial Analytics to Urban Coding and Actual Walking - Elek Pafka; Carlo Andrea Biraghi (Urban Planning, 2025)
Walkability has become a key focus of urban research, linked to the aims of reversing car‐dependence and re‐enabling walking as a healthy, environmentally sustainable and sociable mode of mobility. This thematic issue presents a collection of articles using cutting‐edge research methods ranging from walk‐along interviews to statistical analysis of historic photography, topological and morphological analysis of street networks, and analysis of the spatio‐temporality of various aspects of streetlife. The articles included here provide new insights in understanding morphologies of walkability in cities across the globe. This concise selection of non‐reductionist walkability research reveals the exceptional breadth of research tools, inspiring further methodological innovation, and supporting future urban design and planning practice.